Suppose you have two variables, a and b, both of them nonzero and such that:

a=b

Multiply both sides of the equation by a and you will have:

a2= ab

Subtract b2 from both sides of the equation to obtain:

a2-b2=ab-b2

Factoring both sides of the equation results in:

(a+b)(a-b)=b(a-b)

Divide both sides fo the equation by(a-b) to obtain:

a+b=b

Since we started with the fact that a=b, we can substitute a by b, thus:

b+b=b

It easily follows that 2b=b, thus, dividing both sides by b results n

2=1

I can now tell my employees that that make twice as much as they thought!!!!!